DESCRIPTION OF RISK LEVELS OF GADGET ADDICTION, BULLYING BEHAVIOR, AND DRUG ABUSE IN ADOLESCENTS - Anandayudha, Rama Bagus; Noveriana, Calseries Rizki; Wulandari, Ewin; Tjahjono, Felicia Alvita; Wisnawa, I Wayan Weda; Tiara, Zahra Fadhilazka; Sari, Laprianika Retha Haphita; Dewi, Nurin Kusuma; Alkausar, M. Ramadhan; Augustya, Binnari; Dewayani, Anisa Rahma; Karimah, Azimatul (Universitas Airlangga, 2020)
Gadgets can be interpreted as a tool that can easily be connected to the internet. If the use of gadgets can be done wisely, humans will get many benefits from using gadgets. But if the use of gadgets cannot be controlled, it will have a negative impact. One of the negative effects obtained is dependence or addiction to the gadget itself. Apart from the use of gadgets, bullying is also common today. Approximately three million teenagers become drug abusers in Indonesia. The data was collected using primary data in the form of a questionnaire to collect data on gadget addiction, bullying behavior, and drug abuse among junior high school adolescents at MTs Nahdlatul Wathon Licin. This was a descriptive observational study. The population was students in 8th-9th grades at MTs Nahdlatul Wathon Licin. Sampling was done by total sampling. The number of samples obtained was 93 people. Data were analyzed using descriptive statistical methods which are presented in the form of frequency distribution tables. It was found that 8.6% of respondents had a high risk of gadget addiction, 48.4 % of respondents have a high level of bullying behavior, and 2.2% of respondents are addicted to drugs.